Using Google cloud services to support the activities of the educational institution - Oleksandr V. Babych; Olena V. Babych (Academy of Cognitive and Natural Sciences, 2013)
The total informatization of all aspects of modern society leaves educational institutions no other choice than the equally intensive informatization of all managerial and educational processes. This issue is particularly acute for universities that train IT specialists, because it is better to train future professionals by using the products and technologies with which they will work after graduation. Cloud services are an ideal platform to automate the educational process, because, firstly, they do not require the cost of purchasing hardware and administering a ready-made solution, secondly, they allow a large number of users to collaborate simultaneously, and thirdly, cloud technology is the most fashionable trend right now.